An artificial minority: the stateless Biharis in Bangladesh - Farzana, Kazi Fahmida (Taylor & Francis Group, 2009)
A large number of Biharis who migrated to the former East Pakistan after 1947 have been stranded there since its independence as Bangladesh and separation from Pakistan in 1971.Ever since then, the community has been swaying by the politics of repatriation and hopeless promises.The objective of this paper is to define the status of the Bihari people in Bangladesh. This paper argues that the Bihari community in Bangladesh is an artificial minority because of its social and political context and historical legacy.Despite the fact that they are similar to the majority Bengali people in that they share a common religion, Islam, and have come to share a common language, Bangla, in Bangladesh Biharis are treated differently in terms of identity, nationality, and social, economic and political status.The problem is a result of deliberate procrastination and political indecision on the part of both countries, Bangladesh and Pakistan. However, neither Pakistan nor Bangladesh has done much to resolve the problem of the Bihari community.